Retrieval of coloured dissolved organic matter (CDOM) from MODIS - 272019 Muhammad Yusof Ali (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2008